Morphology of the eggs and larvae of Cyphomyrmex transversus Emery (Formicidae: Myrmicinae: Attini) and a note on the relationship with its symbiotic fungus - Ramos Lacau, Lucimeire de S. [UNESP]; Villemant, Claire; Bueno, Odair C. [UNESP]; Delabie, Jacques H. C.; Lacau, Sebastien (Magnolia Press, 2008)
The morphology of the eggs and larvae of the ant Cyphomyrmex transversus Emery is here described and discussed for the first time. Some morphological characteristics of the symbiotic fungus that covers the eggs, larvae, and pupae are also examined.
Keywords: Formicidae; Myrmicinae; Attini; Cyphomyrmex transversus Emery; immature stages; morphology; symbiotic fungus